IEEE 8th International Symposium on Intelligent Systems and Informatics 2010
DOI: 10.1109/sisy.2010.5647408
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ferrite surface mount bead using S-parameters

Abstract: In this paper, characterization of ferrite surface mount bead based on S-parameters measurement, using vector network analyzer E5071B and specially developed PCB test fixture, are presented. The validation of characterization method was performed using commercially available ferrite component, the surface mount 4-way bead. It is shown that proposed approach is efficient in predicting and analyzing the ferrite bead performance, not only in standard frequency range bellow 100 MHz, but also in high frequency rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The mutual inductance is relatively low, since the conductive lines in ferrite bead are distant from each other, and the coupling between coils is weak. The same conclusion was made in Damnjanovic et al (2010a, b), when the same component was characterized as EMI suppressor. The measured values of transformer TR3 are shown in Figure 10.…”
Section: Measurement and Simulation Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The mutual inductance is relatively low, since the conductive lines in ferrite bead are distant from each other, and the coupling between coils is weak. The same conclusion was made in Damnjanovic et al (2010a, b), when the same component was characterized as EMI suppressor. The measured values of transformer TR3 are shown in Figure 10.…”
Section: Measurement and Simulation Resultssupporting
confidence: 68%
“…Layout for de‐embedding of parasitic effect of the 2‐turns transformers is shown in Figure 7. The procedure of parameter extraction of the ferrite transformer is discussed with more details in Damnjanovic et al (2010a, b). Additionally, in that paper was shown that the de‐embedding of parasitic effects was necessary in the frequency range over 100 MHz, in order to provide accurate enough characterization results.…”
Section: Characterization Methods and Parameter Extraction Of The Ferrite Transformer Based On S‐parameter Measurement Using Vnamentioning
confidence: 99%
See 1 more Smart Citation